Application drought indexes to calculate the drought frequency: Case Study in the Center of Vietnam - D. D. Truong; D. Q. Tri; T. T. Dat; L. T. T. Ha (Lowland Technology International, 2019)
In this paper, we used observation data of rainfall from 1981 to 2016 and average temperature to calculate drought indices: J, Ped, and SPI for the center region of Vietnam. The first advantage of three indicators is that they were based on meteorological variables such as rainfall and average temperature data. The second advantage is that it is possible to estimate the value each month, contributing to the examination of the drought details in a specific period. These indicators easily classify the degree of drought from no drought, normal to moderate and extreme drought. In this study, it is shown that when determined according to the J index, drought is more clearly delineated according to the level of drought. In addition, the J index reflects a significant level of seasonal drought. The result of drought frequency map shows that the extreme drought occurs in the two provinces of Hoi Xuan in Thanh Hoa and Quy Nhon in Binh Dinh. Through the J index, the study also statistically detailed the level of drought for some typical stations in the Central region of Vietnam.